2020
DOI: 10.3390/cancers12102774
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol and Oxygen-Ozone Combination Induce Cytotoxicity in Human Pancreatic Ductal Adenocarcinoma Cell Lines

Abstract: Pancreatic cancer (PC) is related to lifestyle risks, chronic inflammation, and germline mutations in BRCA1/2, ATM, MLH1, TP53, or CDKN2A. Surgical resection and adjuvant chemotherapy are the main therapeutic strategies but are less effective in patients with high-grade tumors. Oxygen-ozone (O2/O3) therapy is an emerging alternative tool for the treatment of several clinical disorders. O2/O3 therapy has been found to ameliorate mechanisms promoting chronic pain and inflammation, including hypoxia, inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 67 publications
(82 reference statements)
2
18
0
Order By: Relevance
“…In vitro studies in MiaPaCa2 and Panc1 cell lines reported that cannabinoid administration led to apoptosis, reduced cell viability and augmented the levels of ceramide and caspase 3. The combination of cannabinoid and O 2 /O 3 induced cytotoxicity and augmented chemosensitivity to gemcitabine and paclitaxel (63). Moreover, mRNA levels of the p8 protein, which is associated with stress, were up-regulated (19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies in MiaPaCa2 and Panc1 cell lines reported that cannabinoid administration led to apoptosis, reduced cell viability and augmented the levels of ceramide and caspase 3. The combination of cannabinoid and O 2 /O 3 induced cytotoxicity and augmented chemosensitivity to gemcitabine and paclitaxel (63). Moreover, mRNA levels of the p8 protein, which is associated with stress, were up-regulated (19).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies investigated cannabinoid receptors in pancreatic cancer both in vitro and in vivo (18,63). Researchers showed that cannabinoid receptors are more highly expressed in human pancreatic tumor cell lines and tumor biopsies than in normal pancreatic tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor cells xenografts transplanted subcutaneously into the immunodeficiency mice have been widely tested in the preclinical studies for identifying or developing the new anticancer drugs (19). The immunodeficient mice such as BALB/c nude mice were the mice that lack T-cell lymphocytes, allowing tumor cell lines to be proliferated and propagated into a solid mass in the subcutaneous region (20,21). The current experiment selected the xenograft tumor model to evaluate the effects of cannabinoid compounds in pancreatic adenocarcinoma transplanted mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that the co-administration of cannabinoids with chemotherapeutic drugs enhanced their efficiency, especially in chemotherapy-refractory tumors [ 10 , 11 ]. Phytocannabinoids may act via dependent and/or independent cannabinoid receptor mechanisms [ 12 , 13 ]. CB1 and CB2 are the first cannabinoids receptors described.…”
Section: Introductionmentioning
confidence: 99%
“…These are G-protein coupled receptors (GPCR) that can be activated by endogenous and exogenous cannabinoids. More recently, studies have shown that cannabinoids can activate other receptors, i.e., GPR55, TRPM8 as well as other ion channels of the transient receptor potential superfamily as vanilloid type 1–4 (TRPV1, TRPV2, TRPV3 and TRPV4) [ 12 , 14 , 15 , 16 , 17 ]. In the context of breast cancer, the biological role of CBD in the regulation of epithelial tumor pathophysiology has clearly emerged [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%